2018
DOI: 10.1021/acs.molpharmaceut.8b00253
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Supersaturation of Nimodipine by PVP with or without the Presence of Sodium Lauryl Sulfate and Sodium Taurocholate

Abstract: Amorphous solid dispersion (ASD) is one of the most versatile supersaturating drug delivery systems to improve the dissolution rate and oral bioavailability of poorly water-soluble drugs. PVP based ASD formulation of nimodipine (NMD) has been marketed and effectively used in clinic for nearly 30 years, yet the mechanism by which PVP maintains the supersaturation and subsequently improves the bioavailability of NMD was rarely investigated. In this research, we first studied the molecular interactions between NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Pinto et al (2019) emphasized the relevance of biorelevant media, as they revealed specific interactions between polymer and surfactants, which led to a decreased supersaturation performance in FaSSIF compared to plain buffer [43]. In line with this, Pui et al also found a decreased supersaturation ability of a polymer due to competitive interactions with surfactants [44]. Consequently, the HPMCAS concentration needed to be increased to 3.6 mg/mL in presence of FaSSIF.…”
Section: Discussionmentioning
confidence: 89%
“…Pinto et al (2019) emphasized the relevance of biorelevant media, as they revealed specific interactions between polymer and surfactants, which led to a decreased supersaturation performance in FaSSIF compared to plain buffer [43]. In line with this, Pui et al also found a decreased supersaturation ability of a polymer due to competitive interactions with surfactants [44]. Consequently, the HPMCAS concentration needed to be increased to 3.6 mg/mL in presence of FaSSIF.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the authors reported enhanced dissolution profiles for Eudragit EPO with the NSAIDs (non-steroidal anti-inflammatory drugs) indomethacin and piroxicam. There are also indications that a nonspecific binding can result in a crystallization inhibition effect (Baghel et al, 2018): an NMR study on nimodipine with PVP (polyvinylpyrrolidone) as a polymer in solution showed nonspecific hydrophobic interactions between the hydrophobic moieties of the polymer and the drug (Pui et al, 2018). A study investigating the higher degree of crystallization inhibition by PAA (polyacrylic acid) compared to PVP concluded that this effect is attributed to strong specific interactions between drug and polymer as observed with NMR measurements.…”
Section: Supersaturation Stabilization By Polymersmentioning
confidence: 97%
“…Compared to its crystalline counterpart, an amorphous drug exhibits higher “kinetic solubility” owing to its high free energy and metastable nature [ 20 ]. Despite this beneficial aspect, the amorphous drug can undergo precipitation upon wetting–dissolution of ASD particles, which detrimentally affects its physical stability and sustained supersaturation capability [ 20 , 21 ]. Supersaturation is desirable for the absorption and bioavailability of the drug if it is sustained over a gastrointestinal transition time of 4–5 h. Supersaturation, albeit desirable on its own, is also the driving force for primary or secondary nucleation (in the presence of residual crystals) [ 22 ], followed by growth and aggregation of precipitated particles, which can cause depletion of initially high supersaturation or a lower extent of dissolution [ 20 , 21 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this beneficial aspect, the amorphous drug can undergo precipitation upon wetting–dissolution of ASD particles, which detrimentally affects its physical stability and sustained supersaturation capability [ 20 , 21 ]. Supersaturation is desirable for the absorption and bioavailability of the drug if it is sustained over a gastrointestinal transition time of 4–5 h. Supersaturation, albeit desirable on its own, is also the driving force for primary or secondary nucleation (in the presence of residual crystals) [ 22 ], followed by growth and aggregation of precipitated particles, which can cause depletion of initially high supersaturation or a lower extent of dissolution [ 20 , 21 , 23 , 24 , 25 ]. Depending on their concentration and interactions with the drug, polymers in ASDs can inhibit drug precipitation, affording the sustainment of the drug supersaturation [ 23 , 24 ] besides their role in ASD formation through polymer–drug miscibility.…”
Section: Introductionmentioning
confidence: 99%